The Development of Strategies for Driving the Philosophy of Sufficiency Economy in the Occupation of Growing Economic Crops for Farmers in Muang Phai Sub-district, Nong Ki District, Buriram Province - Sakultong, Amnat; Kittichasri, Damrong; Sritawann, Banyong; Sawangtap , Jarous (Academic MCU Buriram Journal, 2021)
The aims of this research are as follows: 1) to study the general context and problem situation of Muang Phai Subdistrict, Nong Ki District, Buriram Province; 2) to formulate strategies for driving the philosophy of sufficiency economy in farmers' careers and 3) to study the operational guidelines in response to the strategy. The instruments used in this research were questionnaires, observational and group chat. Develop strategies by using SWOT analysis methods and seminars based on experts. The research result finds that: 1. Muang Phai Subdistrict is a plateau area. It has a tropical monsoon climate. The soil is a sandy clay soil. There are 19 natural and built water bodies, but now the natural bodies of water cannot hold water all year round. Most farmers grow rice, sugarcane, cassava, vegetables and raise animals. There are some farmers who do not have their own arable land and have to rent their arable land. 2. Development of 3 strategies: Strategy 1: Increase production efficiency and raise product standards by adopting modern agricultural technology and innovations to get more productivity per rai. Strategy 2 Add value of agricultural products bring academic knowledge, science, technology and innovation. Local wisdom in agriculture to produce and process products to increase local value and identity. Strategy 3 Management of agricultural and environmental resources. Promote environmentally friendly agriculture. Total water management system allocation of arable land in public areas in the form of community housing. 3. Guidelines for action to meet the strategy. It was found that the driving strategy for farmers. There must be a systematic, connected and continuous action strategy. Must coordinate cooperation throughout the system from many parties, both government agencies local government organization, entrepreneur, farmer and consumer to community leader.